Biochemical characterization of β-lactamases from mycobacterium abscessus complex and genetic environment of the β-lactamase-encoding gene - Ramírez, Ana (2017)
The objectives of this study were to determine the kinetic parameters of purified recombinant BlaMab and BlaMmas by spectrophotometry, analyze the genetic environment of the blaMab and blaMmas genes in both species by polymerase chain reaction and sequencing, furthermore, in silico models of both enzymes in complex with imipenem were obtained by modeling tools. Our results showed that BlaMab and BlaMmas have a similar hydrolysis behavior, displaying high catalytic efficiencies toward penams, cephalothin, and nitrocefin; none of the enzymes are well inhibited by clavulanate. BlaMmas hydrolyzes imipenem at higher efficiency than cefotaxime and aztreonam. BlaMab and BlaMmas showed that their closest structural homologs are KPC-2 and SFC-1, which correlate to the mild carbapenemase activity toward imipenem observed at least for BlaMmas. They also seem to differ from other class A β-lactamases by the presence of a more flexible Ω loop, which could impact in the hydrolysis efficiency against some antibiotics. A -35 consensus sequence (TCGACA) and embedded at the 3′ end of MAB-2874, which may constitute the blaMab and blaMmas promoter. Our results suggest that the resistance mechanisms in fast-growing mycobacteria could be probably evolving toward the production of β-lactamases that have improved catalytic efficiencies against some of the drugs commonly used for the treatment of mycobacterial infections, endangering the use of important drugs like the carbapenems.